Targeted search of hypoglycemic agents among N-substituted isoindoline-1,3-diones and its analogues - Yu. V. Martynenko; M. S. Kazunin; O. M. Antypenko; Ye. A. Selivanova; S. I. Kovalenko; S. D. Trzhetsynskyi (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
It is known, that increasing of glucose level in the blood is an important factor at the risk of vascular complications in diabetes mellitus type 2 development. Taking this into account, short-acting priming regulators of glycemia (meglitinides) are designed, such as tableted sugar-reducing drugs with short acting insulin secretion stimulation. They are characterized by a slight decrease of glycohemoglobin content, the risk of body weight gain and decrease of efficacy during long-term usage despite their effectiveness. The solution of this problem can be as following: the creation of more effective drugs, which would contain known antidiabetic “pharmacophore” fragments able to provide a long-term hypoglycemic effect and having a polyvectoral mechanism of activity and effect both on symptoms of the disease and on disease etiology.